Facile deposition of palladium oxide (PdO) nanoparticles on CoNi2S4 microstructures towards enhanced oxygen evolution reaction. (2nd July 2022) - Tahira, Aneela; Aftab, Umair; Solangi, Muhammad Yameen; Gradone, Alessandro; Morandi, Vittorio; Medany, Shymaa S; Kasry, Amal; Infantes-Molina, Antonia; Nafady, Ayman; Ibupoto, Zafar Hussain
Abstract: Strong demand for renewable energy resources and clean environments have inspired scientists and researchers across the globe to carry out research activities on energy provision, conversion, and storage devices. In this context, development of outperform, stable, and durable electrocatalysts has been identified as one of the major objectives for oxygen evolution reaction (OER). Herein, we offer facile approach for the deposition of few palladium oxide (PdO) nanoparticles on the cobalt–nickel bi-metallic sulphide (CoNi2 S4 ) microstructures represented as PdO@ CoNi2 S4 using ultraviolet light (UV) reduction method. The morphology, crystalline structure, and chemical composition of the as-prepared PdO@ CoNi2 S4 composite were probed through scanning electron microscopy, powder x-ray diffraction, high resolution transmission electron microscopy, energy dispersive spectroscopy and x-ray photoelectron spectroscopy techniques. The combined physical characterization results revealed that ultraviolet light (UV) light promoted the facile deposition of PdO nanoparticles of 10 nm size onto the CoNi2 S4 and the fabricated PdO@ CoNi2 S4 composite has a remarkable activity towards OER in alkaline media. Significantly, it exhibited a low onset potential of 1.41 V versus reversible hydrogen electrode (RHE) and a low overpotential of 230 mV at 10 mA cm −2 . Additionally, the fabricated PdO@ CoNi2 S4 composite has a marked stability of 45 h. Electrochemical impedance spectroscopy has shown that the PdO@CoNi2 S4 composite has a low charge transfer resistance of 86.3 Ohms, which favours the OER kinetics. The PdO@ CoNi2 S4 composite provided the multiple number of active sites, which favoured the enhanced OER activity. Taken together, this new class of material could be utilized in energy conversion and storage as well as sensing applications.